Low-severity wildfire prevents catastrophic impacts on fungal communities and soil carbon stability in a fire-affected Douglas-fir ecosystem - Timothy J. Philpott; Gabriel Danyagri; Brian Wallace; Mae Frank (Geoderma)
The growing frequency, extent and severity of wildfire is destabilizing carbon sinks in western North America, underscoring an urgent need to better understand fire impacts on soil carbon stocks, carbon stability, and fungi that regulate soil carbon cycling. Here, we examined the effects of wildfire two years post-burn on soil carbon and fungal communities across a fire severity gradient in Douglas-fir forests in central British Columbia, Canada. We observed no significant differences in soil carbon or fungal community composition between low-severity and unburned stands. In contrast, high-severity wildfire resulted in a 49 % reduction in belowground carbon stocks (20.7 Mg C·ha−1), a 91 % decline in ectomycorrhizal fungi, 5- to 27-fold increases in pathogenic fungi, and a proliferation of pyrophilous taxa compared to unburned stands. Carbon was lost primarily as light particulate organic matter, whereas impacts to mineral-associated carbon were muted. Pyrogenic carbon preferentially associated with the mineral fraction, modestly increasing (∼0.15 Mg C·ha−1) the proportion of carbon resistant to decay in this stable fraction. Select helotialean (e.g. Phialocephala fortinii) and other pyrophilous taxa were well-correlated with pyrogenic carbon, suggesting this consortium is well-adapted to decompose persistent carbon and will likely continue to mineralize soil carbon even after high severity wildfire. The markedly higher abundance of pathogenic fungi and reduced ectomycorrhizal abundance in stands affected by high-severity fires pose risks to post-fire recovery, particularly if pathogen proliferation reduces conifer fitness. These results highlight that low-severity wildfires have comparatively muted impacts on soil carbon and fungal communities relative to high-severity wildfires, underscoring the importance of management strategies such as thinning and prescribed burns to mitigate the catastrophic effects of high-severity wildfires.